2018
DOI: 10.1007/978-3-319-74424-7_11
|View full text |Cite
|
Sign up to set email alerts
|

France 2072: Lifestyles at the Core of Carbon Neutrality Challenges

Abstract: In this chapter, we propose to explore the conditions under which a stringent target of 1.5°C-written into the Paris Agreement in December 2015-may be fulfilled at a country level, France, while focusing on energy issues. The analysis horizon spans to 2072 in reference to the Club of Rome's 1972 Limits to Growth publication, 2072 being the neutral target. To this end, we explore the impact of two contrasting lifestyles for France: the first, named digital, represents an individualistic and technological societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Considering only the IAM and ESM-based applications, the percentage of global-level studies was higher than that of national-level studies due to the wider system boundaries defined in these modeling frameworks. The majority of the national and sub-national studies in the complete sample (~80%) were performed for countries located in the Global North, which consist mainly of developed OECD (Organisation for Economic Co-operation and Development) economies (e.g., USA [39], United Kingdom [40], Japan [41] and a number of EU member states [42]). On the other hand, only a few modeling studies were identified with a focus on developing or less-developed nations (e.g., China [43] and India [44]).…”
Section: General Statistics Of the Reviewed Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering only the IAM and ESM-based applications, the percentage of global-level studies was higher than that of national-level studies due to the wider system boundaries defined in these modeling frameworks. The majority of the national and sub-national studies in the complete sample (~80%) were performed for countries located in the Global North, which consist mainly of developed OECD (Organisation for Economic Co-operation and Development) economies (e.g., USA [39], United Kingdom [40], Japan [41] and a number of EU member states [42]). On the other hand, only a few modeling studies were identified with a focus on developing or less-developed nations (e.g., China [43] and India [44]).…”
Section: General Statistics Of the Reviewed Papersmentioning
confidence: 99%
“…Limiting unnecessary floor area per capita through, for example, compact city and building designs, is represented by setting a cap on household areas in the majority of lifestyle-led mitigation pathways [19,28] according to living standards in selected developed economies. Contrary to the customary approach, the authors of [42,90] established a statistical relationship between housing floor area and a set of factors, such as cohabitation practices and dwelling location, based on information from national surveys in France. By changing the strength of the statistical relationship, the authors simulated the potential effects of lifestyle changes on household floor area, which were then fed as inputs to an energy-system model to analyze the wider effects on energy use and emissions.…”
Section: Modeling Lifestyle Changes In the Residential Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Significant lifestyle change is required to reduce future energy and emission outcomes consistent with Paris Climate Agreement goals to limit global warming to well below 2 • C [1][2][3][4][5]. The Sixth Assessment Report of the IPCC suggests that by 2050, global CO 2 emissions could be reduced 40%-70% across all enduse sectors with demand-based mitigation strategies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Social actors at each of these levels have different interests, political beliefs, belong to different social classes, and represent various sectors (professional, business, cultural, spatial) of society. Hence, it is worth recalling and emphasising that energy transition is not only the replacement of one energy generation technology by another, but a complex social process affecting not only the natural environment, but also production models, employment structure, safety and workplace costs [7], international political alliances and geopolitical systems [8], power systems and relations [9], the strategies of entrepreneurs [10], the lifestyle and consumption behaviour of citizens [11,12] and dozens of other dimensions of social life. These diverse factors-including, primarily, geopolitical risk and international uncertainty [13]-may not only be affected by energy transition, but may themselves accelerate or delay the transition to renewable energy.…”
Section: Introductionmentioning
confidence: 99%